Integrated approaches for increasing plant yield under salt stress - Ahmad, Irshad; Zhu, Guanglong; Zhou, Guisheng; Younas, Muhammad Usama; Suliman, Mohamed Suliman Eltyeb; Liu, Jiao; Zhu, Yi ming; Salih, Ebtehal Gabralla Ibrahim (Frontiers in Plant Science, 2023)
Salt stress affects large cultivated areas worldwide, thus causing remarkable reductions in plant growth and yield. To reduce the negative effects of salt stress on plant growth and yield, plant hormones, nutrient absorption, and utilization, as well as developing salt-tolerant varieties and enhancing their morpho-physiological activities, are some integrative approaches to coping with the increasing incidence of salt stress. Numerous studies have been conducted to investigate the critical impacts of these integrative approaches on plant growth and yield. However, a comprehensive review of these integrative approaches, that regulate plant growth and yield under salt stress, is still in its early stages. The review focused on the major issues of nutrient absorption and utilization by plants, as well as the development of salt tolerance varieties under salt stress. In addition, we explained the effects of these integrative approaches on the crop's growth and yield, illustrated the roles that phytohormones play in improving morpho-physiological activities, and identified some relevant genes involve in these integrative approaches when the plant is subjected to salt stress. The current review demonstrated that HA with K enhance plant morpho-physiological activities and soil properties. In addition, NRT and NPF genes family enhance nutrients uptake, NHX1, SOS1, TaNHX, AtNHX1, KDML, RD6, and SKC1, maintain ion homeostasis and membrane integrity to cope with the adverse effects of salt stress, and sd1/Rht1, AtNHX1, BnaMAX1s, ipal-1D, and sft improve the plant growth and yield in different plants. The primary purpose of this investigation is to provide a comprehensive review of the performance of various strategies under salt stress, which might assist in further interpreting the mechanisms that plants use to regulate plant growth and yield under salt stress.